Genome-Wide Analysis of Soybean JmjC Domain-Containing Proteins Suggests Evolutionary Conservation Following Whole-Genome Duplication - Han, Yapeng; Li, Xiangyong; Cheng, Lin; Liu, Yanchun; Wang, Hui; Ke, Danxia; Yuan, Hongyu; Zhang, Liangsheng; Wang, Lei (Frontiers in Plant Science, 2016)
Histone modifications, such as methylation and demethylation, play an important role in regulating chromatin structure and gene expression. The JmjC domain-containing proteins, an important family of histone lysine demethylases (KDMs), play a key role in maintaining homeostasis of histone methylation in vivo. In this study, we performed a comprehensive analysis of the jumonji C (JmjC) gene family in the soybean genome and identified 48 JmjC genes (GmJMJs) distributed unevenly across 18 chromosomes. Phylogenetic analysis showed that these JmjC domain-containing genes can be divided into eight groups. GmJMJs within the same phylogenetic group share similar exon/intron organization and domain composition. In addition, 16 duplicated gene pairs were formed by a Glycine-specific whole-genome duplication (WGD) event approximately 13 million years ago (Mya). By examining the expression of these gene pairs in various tissues, we showed that the expression pattern is conserved in the polyploidy-derived JmjC duplicates, demonstrating that the majority of GmJMJs were preferentially retained after the most recent WGD event and suggesting important roles for demethylase duplications in soybean evolution. These results shed light on the evolutionary history of this family in soybean and provide insights into the JmjCs which will be helpful to reveal their functions in controlling soybean development.